DO BELIEFS THAT OLDER ADULTS ARE INFLEXIBLE SERVE AS A BARRIER TO RACIAL EQUITY?. (20th December 2022) - Chaney, Kimberly; Chasteen, Alison
Abstract: Past research has demonstrated that older adults are stereotyped as less malleable than younger adults, such that older adults are perceived to be less capable of changing their beliefs and learning new things. Moreover, beliefs that people are less malleable are associated with lower confrontations of prejudice, as perpetrators are seen as less capable of changing their (prejudiced) behavior. The aim of the present research was to integrate these lines of research to demonstrate that endorsement of ageist beliefs that older adults are less malleable will lead to lower confrontation of anti-Black prejudice espoused by older adults. Across four experimental studies (N = 1, 310), people were less likely to confront anti-Black prejudice espoused by an 82 year-old compared to a 62, 42, or 20 year-old, due, in part, to beliefs that older adults are less malleable. Further exploration demonstrated that malleability beliefs about older adults were held across young, middle-aged, and older adult samples, though older participants were the least likely to confront prejudice, regardless of perpetrator age. Alternative mechanisms are explored, including respect, perceived social influence, and perceived awareness of egalitarian norms. These findings demonstrate how stereotypes about older adults can impede racial equality and highlight that interventions geared towards reducing ageism could, in turn, lead to greater racial equality.